PENGARUH RELATIONSHIP MARKETING TERHADAP KEPUASAN NASABAH DAN LOYALITAS NASABAH BANK RAKYAT INDONESIA DI SULAWESI TENGGARA - Sudirman Zaid (EKUITAS (Jurnal Ekonomi dan Keuangan), 2007)
This research is intended to test the effect of relationship marketing upon customer satisfaction and customer loyalty of the Bank Raykat Indonesia in Southeast Sulawesi. This research applies the explanatory type, namely a research conducted by giving an explanation on the symptoms produced by object of research.The samples of this research involve 200 saving deposits customer of Bank Rakyat Indonesia distributed based on purposive allocation of each Bank Rakyat Indonesia in Southeast Sulawesi. Then, they are analyzed by using SEM (structural equation modeling) by applying the program AMOS (analysis of moment structure) 4.01.The result of this research indicate that the relationship marketing have the positive and significant effect to the customer satisfaction and customer loyalty with the path coefficient each 0.556 and 0.501. And than, customer satisfaction have the positive and significant effect to the customer loyalty with the path coefficient 0.479. Beside that, the relationship marketing have the indirect effect to the customer loyalty, mediated customer satisfaction with the path coefficient 0.266.